Prevalence of and Factors Associated with Depression in Patients with Schizophrenia in a University Hospital: A Post-hoc Analysis - Suttajit, Sirijit; Pilakanta, Sutrak (Biomedical Sciences and Clinical Medicine, 2024)
Objectives This study was aimed to assess the prevalence of depression and identify factors associated with depression in patients with schizophrenia in a university hospital. Methods This was a post-hoc analysis of a cross-sectional study conducted in 75 patients with schizophrenia. Major depressive episodes were diagnosed according to DSM-IV-TR. The six social support deficits (SSDs) scale was used to identify social support deficits. Chisquare and logistic regression were used to determine factors associated with depression. Results The prevalence of depression was 16.0%, with only 25.0% of them previously being recognized and treated with antidepressants. Age, sex, marital status, income, duration of illness, type of antipsychotic drugs and number of side effects were not significantly associated with depression. Three out of six social support deficits were associated significantly with depression, including living alone, reciprocity in the family, and dissatisfaction with family support, with odds ratios of 10.0, 4.9 and 8.6, respectively. Those with at least one social support deficit were 9.3 times more likely to be depressed than those without one (p=0.002). Conclusion This study suggested that depression in patients with schizophrenia was still under recognized by Thai psychiatrists. The findings do not support the hypothesis that depression is more common in patients receiving typical antipsychotic drugs. Psychosocial factors such as social support deficits were found to have a higher impact on depression than biological ones in Thai patients with schizophrenia.